Validation of the SF-6D Health State Utilities Measure in Lower Extremity Sarcoma. (19th March 2014) - Gundle, Kenneth R.; Cizik, Amy M.; Punt, Stephanie E. W.; Conrad, Ernest U.; Davidson, Darin J.
Abstract : Aim . Health state utilities measures are preference-weighted patient-reported outcome (PRO) instruments that facilitate comparative effectiveness research. One such measure, the SF-6D, is generated from the Short Form 36 (SF-36). This report describes a psychometric evaluation of the SF-6D in a cross-sectional population of lower extremity sarcoma patients. Methods . Patients with lower extremity sarcoma from a prospective database who had completed the SF-36 and Toronto Extremity Salvage Score (TESS) were eligible for inclusion. Computed SF-6D health states were given preference weights based on a prior valuation. The primary outcome was correlation between the SF-6D and TESS. Results . In 63 pairs of surveys in a lower extremity sarcoma population, the mean preference-weighted SF-6D score was 0.59 (95% CI 0.4–0.81). The distribution of SF-6D scores approximated a normal curve (skewness = 0.11). There was a positive correlation between the SF-6D and TESS (r = 0.75, P < 0.01 ). Respondents who reported walking aid use had lower SF-6D scores (0.53 versus 0.61, P = 0.03 ). Five respondents underwent amputation, with lower SF-6D scores that approached significance (0.48 versus 0.6, P = 0.06 ). Conclusions . The SF-6D health state utilities measure demonstrated convergent validity without evidence of ceiling or floor effects. The SF-6D is a health state utilities measure suitable for further research in sarcoma patients.